KEPERCAYAAN DIRI SISWA MELALUI PENGGUNAAN MEDIA BELAJAR LUDO FAUNA (Studi Narrative Inquiry mengenai hewan di sekitar pada siswa Sekolah Dasar) - Khoirunnisa, Siti; Wuryastuti, Sri; Suratno, Tatang (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Confidence is the most important thing that every primary school student has because a confident student will easily determine their future such as goals, goals, and achievements. A confident person who dares to make decisions dare to speak or argue can face any situation. And is confident in himself. Meanwhile, students who are not confident will experience a lack such as being left behind in terms of learning activities in school. Learning methods or media have a very important role in the learning process, in addition to achieving the purpose of media learning is also a thing that can attract the attention and desire of students in learning and can motivate students. This study aims to find out the factors that cause elementary school students to be confident and not confident and how confident students are through the use of learning media ludo fauna. The approach used in this study is a qualitative research approach with a narrative inquiry method. This research uses data collection techniques, namely observation, interview, documentation, field note, and storytelling. As well as instruments used in the form of recording and interview tools. The results of this study are factors that can cause students confidence that is a pleasant and comfortable class. Then what causes students not confidence is fear of wrong, in the attention of friends, forward class, and appointed teachers. Through the use of learning media ludo fauna has seen an increase in confidence as students have dared to issue their opinions and ask if there are things that do not understand. Not only that, but students also look very enthusiastic, happy, and excited.